Influence of Practice Periodization and Sleep Duration on Oxidative Stress in High School Judo Athletes - Ena Yoshida; Harumi Hayashida (MDPI AG, 2023)
Numerous research studies have investigated the relationship between exercise, oxidative stress level, and condition in athletes who engage in intense training on a daily basis. However, it is known that oxidative stress is affected by exercise, sleep, and the psychological state, but there are only a few studies that have comprehensively examined oxidative stress based on the actual practice periods and living conditions of athletes. Therefore, our study aimed to explore the influence of three distinct training periods (short training period, intensive training period, and pre-competition periods) as well as life situations (sleep and number of steps) on oxidative stress levels (diacron reactive oxygen metabolites: d-ROMs) in high school judo athletes. The results showed that, among the three periods, the level of oxidative stress increased the most during the pre-competition period, and the value was higher than during the training period, when the intensity of training was highest. The levels of the d-ROMs values during the pre-competition period were negatively correlated with the amount of sleep on the previous day. The findings suggest that, besides the exercise intensity, factors such as sleep duration and other life situations should be regarded as critical considerations for high school judo athletes.